Conceptualizing value co-creation for service innovation in academic libraries. (March 2015) - Islam, Md Anwarul; Agarwal, Naresh Kumar; Ikeda, Mitsuru
For the academic library to remain relevant to its users, it must redefine its role in the digital environment and innovate to create responsive and convenient services. It must work actively not just to create value for the user but to involve the user in value co-creating value for service innovation. In this theoretical work, we conceptualize the business concept of value co-creation in the context of libraries and propose a framework of value co-creation for service innovation in academic libraries. With guidance on value co-creation in an academic library environment, and library actors mapped to the co-creation cycle, libraries can use the framework to offer new library services to user communities. The framework also provides a basis for further research in this area.